INFORMATIONAL AND LIBRARY SUPPORT OF EDUCATIONAL ACTIVITIES AND SCIENTIFIC RESEARCH - T. N. STUKALOVA; I. P. KAPOCHKINA (Moscow Polytechnic University, 2017)
The article describes the history, activities, and major achievements of the library of the National Research Nuclear University MEPhI. Since 2011 the library has the status of a Centre for informational and library support of the teaching and research activities of the University. Its main objective is to form the unified information space with the equal possibilities for all user categories irrespectively of their location. This is provided by the Electronic Library System. The MEPhI Library widely uses the new technologies, innovative forms of service such as the sub-system "Textbook provision of the learning process" functioning on the principle of multitasking. Due to MEPhI's participation in the Program 5-100 the library has optimized the access system to scientific data bases especially to foreign citation bases such as Web of Science and Scopus. Information and library support of educational activities and scientific research significantly promotes raising of publication activities of the University researchers and teaching staff.